Incidence, indications, and outcomes of emergency peripartum hysterectomy in Africa: A systematic review and meta-analysis - Mulat Ayele; Eyob Shitie Lake; Befkad Derese Tilahun; Abebaw Alamrew; Chalie Mulugeta; Esuyawukal Mislu; Tegene Atamenta; Gizachew Yilak (Heliyon, 2025)
Introduction: Even though emergency peripartum hysterectomy is a lifesaving procedure for the various life threatening indications, its incidence is increasing resulting with various intra and post-operative maternal and perinatal complication. The incidence, indication and outcomes of emergency peripartum hysterectomy are the indicators of quality of maternal care and also vary in different African countries. Therefore this systematic review and meta-analysis aimed to assess the pooled incidence, indication and outcomes of emergency peripartum hysterectomy in Africa. Objective: To assess the pooled incidence, indication and outcomes of emergency peripartum hysterectomy in Africa. Methods: A comprehensive search was done in PubMed, Cochrane Library, Hinari, Google Scholar, CINAHL, and Scopus between November 10 and 20, 2024 using searching terms. The quality of the included studies was assessed using Newcastle-Ottawa Quality Assessment Scale. Random effect model were used to estimate the pooled incidence using Stata version 17. Higgins's I2 statistics, subgroup analysis, and publication bias was done accordingly. Result: This systematic review and meta-analysis included 25 studies with a total of 611,704 participants. The pooled incidence of emergency peripartum hysterectomy among delivered mothers in Africa was 2.12 per 1000 delivered women (95 % CI: 2.00–2.33), with a heterogeneity index of I2 = 93.07 %, P = 0.00. A higher incidence of emergency peripartum hysterectomy was observed in West Africa (3.02 per 1000; 95 % CI: 2.47–3.58), and lower in South Africa (2.43 per 1000; 95 % CI: 0.54–4.32). The most common indications for emergency peripartum hysterectomy were uterine rupture (44.96 %; 95 % CI: 34.96–55.28), uterine atony (29 %; 95 % CI: 22.31–35.7), and placenta accreta spectrum (15.71 %; 95 % CI: 10.65–20.78). The most common outcomes of emergency peripartum hysterectomy were maternal mortality (8.19 %; 95 % CI: 6.81–9.57), perinatal mortality (50.59 %; 95 % CI: 38.9–62.28), maternal sepsis (18.87 %; 95 % CI: 16.61–21.21), maternal severe anemia (71.26 %; 95 % CI: 67.43–75.09), disseminated intravascular coagulopathy (8 %; 95 % CI: 3.59–14.01), and urinary tract injury (3.99 %; 95 % CI: 2.60–5.38). Conclusion: The incidence of emergency peripartum hysterectomy in Africa was higher compared to developed countries. Uterine rupture, uterine atony and placental accreta spectrum were the most common indication for emergency peripartum hysterectomy respectively. The maternal and perinatal mortality and morbidity was higher in Africa. This is due to poor quality of intrapartum, intraoperative and post-operative care in Africa. Therefore, capacity building in evidence based practice among the professionals to give the quality maternal care is needed.